USE OF PORTRAITS IN TRADEMARKS (STUDY ON THE CASE OF THE USE OF MRS MENEER'S PORTRAIT) - Fitrianda, Widiya; Sunarmi, Sunarmi; Saidin, Saidin (Inspiring Law Journal, 2024)
The use of portraits in trademarks creates polemics because copyright and trademarks are part of the IPR regime which have different protection concepts and objectives. This research aims to determine, examine and analyze the legal arrangements regarding the transfer of rights to the trademark